Scientific Identification of Lacunarity in Languages with Different Structures (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Lacunarity, a concept originating in fractal geometry, has been adapted in linguistic studies to describe the presence of gaps, asymmetries, or untranslatable elements in language systems. This article explores the manifestation and identification of lacunarity in structurally diverse languages, with a focus on syntactic, morphological, and lexical domains. Drawing on recent literature and cross-linguistic analyses, the study presents a methodology for identifying lacunarity through comparative linguistic research. The findings highlight the implications for translation studies, second language acquisition, and cognitive linguistics. The study contributes to a deeper understanding of linguistic relativity and structural divergence, encouraging further empirical research.